A Heuristic Inquiry into my use of Theraplay® with children experiencing the impact of relational and developmental trauma - Peacock, Fiona (European Journal for Qualitative Research in Psychotherapy, 2023)
In this paper, I share my process of conducting doctoral research using Heuristic Inquiry. As a practising Theraplay® counsellor/psychotherapist working with children who are experiencing relational and developmental trauma, I start by locating myself in the research and explain Theraplay as a model. Heuristic Inquiry is then used to examine my own practice, and what this process of research illuminated for me. Specifically, the use of tacit maternal knowing - a way to use maternal wisdom in the professional realm as a de-gendered, de-sexed skill - is theorised. I explain why, in my opinion, trying to understand how and why Theraplay works for children experiencing relational and developmental trauma via a perspective that seeks to find the answer that is generalisable and manualisable is inappropriate for this form of work. This paper will be of benefit to: those wishing to research their own therapeutic practice in a way that honours the uniqueness of the therapeutic relationship between client and therapist; those wishing to use Heuristic Inquiry as a research methodology; those wishing to research using arts-based methods; and practitioners interested in Theraplay as a model of work for this clinical population. It argues that employing creative methods of research is congruent with modes of therapeutic work.